At Least 55 Undeclared Chemical Elements Found in COVID-19 Vaccines from AstraZeneca, CanSino, Moderna, Pfizer, Sinopharm and Sputnik V, with Precise ICP-MS - Diblasi, Lorena (2024)
The experimental vaccines supposedly invented to combat COVID-19 were coercively forced upon the global population beginning late in 2020. They have precipitated innumerable and varied disease conditions ranging from mild to lethal. This increase in health disorders and sudden deaths began to manifest concomitantly with the number of people inoculated and doses administered per person. By the end of 2023, 24 undeclared chemical elements had been detected by Scanning Electron Microscopy Coupled with Energy-Dispersive X-Ray Spectroscopy (SEM-EDX), in the COVID-19 vaccines of the different brands, by various research groups from different countries around the world. In this paper, we report laboratory results from high precision Inductively Coupled Plasma Mass Spectrometry (ICP-MS) that confirm and expand previous results by SEM-EDX. To this end, the contents of vials from different lots of the brands AstraZeneca/Oxford, CanSino Biologics, Pfizer/BioNTech, Sinopharm, Moderna and Sputnik V were analyzed. Among the undeclared chemical elements were detected 11 of the 15 cytotoxic lanthanides used in electronic devices and optogenetics. In addition, among the undeclared elements were all 11 of the heavy metals: chromium was found in 100% of the samples; arsenic 82%; nickel 59%; cobalt and copper 47%; tin 35%; cadmium, lead and manganese in 18%; and mercury in 6%. A total of 55 undeclared chemical elements were found and quantified with ICP-MS. Combining these findings with results from SEM-EDX, altogether 62 undeclared chemical elements have been found in the various products. In all brands, we found boron, calcium, titanium, aluminum, arsenic, nickel, chromium, copper, gallium, strontium, niobium, molybdenum, barium and hafnium. With ICP-MS, we found that the content of the samples is heterogeneous, the elemental composition varies in different aliquots extracted from the same vial.